Ibuprofen-Induced Multiple Fixed Drug Eruption Confirmed by Re-Challenge: A Case Report and Literature Review - Yoshihito Mima; Masako Yamamoto; Hiyo Obikane; Yuta Norimatsu; Ken Iozumi (Diagnostics)
Background: Fixed drug eruption (FDE) is a type of drug-induced skin inflammation characterized by the recurrence of lesions in the same region following repeated exposure to the causative drug. FDE typically presents as localized spots or plaques without systemic symptoms; however, it can manifest in other forms, such as blisters and papules. In FDE, effector memory CD8-positive T cells that remain dormant in the basal layer after a previous inflammation are reactivated upon re-exposure to the causative drug, leading to the development of erythema at the same sites. Case Presentation: Herein, we report the case of a 23-year-old man who developed ibuprofen-induced multiple FDE. The diagnosis was confirmed by detecting a rash immediately following ibuprofen administration, and histopathological findings were consistent with FDE. Ibuprofen is widely available as an over-the-counter medication, and patients may not always report its use—making the diagnosis of ibuprofen-induced FDE particularly challenging. Approximately 24 h following drug-induced CD8-positive T cell activation, regulatory T cells normally infiltrate the epidermis to suppress inflammation and promote resolution. However, in multiple FDE, CD8-positive T cell activity may outweigh that of regulatory T cells, causing uncontrolled inflammation and leading to the spread of poorly-demarcated lesions that can progress to severe drug reactions such as Stevens–Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN). We reviewed 13 cases of ibuprofen-induced multiple FDE. Conclusions: Over-the-counter medications can cause multiple FDEs, and the repeated administration of the causative drug can result in severe reactions such as SJS/TEN. The early diagnosis and strict discontinuation of the causative drugs are therefore crucial.